Cross-sectional study of conjugated linoleic acid in adipose tissue and risk of diabetes(1)(2)(3) - Castro-Webb, Nelsy (American Society for Nutrition, 2012)
Background: Some experimental studies on conjugated linoleic acid (CLA) and insulin regulation suggested that CLA could be associated with risk of diabetes, but epidemiologic studies are lacking. Objective: The aim of the study was to test whether the amount of CLA in adipose tissue is associated with risk of diabetes. Design: A cross-sectional design was used to test the study hypothesis in 232 adults with diabetes and 1512 adults without diabetes who lived in Costa Rica. The cis-9, trans-11 and trans-10, cis-12 CLA isomers in adipose tissue and 48 other fatty acids were assessed by using gas chromatography. Prevalence ratios (PRs) and 95% CIs were estimated by using Poisson regression adjusted for potential confounders. Results: The mean (±SD) percentage of total fatty acids of CLA for the cis-9, trans-11 isomer in adipose tissue was 0.57 ± 0.18% in adults without diabetes and 0.53 ± 0.17% in adults with diabetes (P = 0.0078). The trans-10, cis-12 CLA isomer was not detected in adipose tissue. The cis-9, trans-11 CLA isomer was associated with a lower risk of diabetes. In comparison with the first quintile, the PR (95% CI) for the fifth quintile was 0.48 (0.31, 0.76) (P-trend = 0.0005) in the basic and 0.46 (0.29, 0.72) (P-trend = 0.0002) in the multivariable model. Additional adjustment for other fatty acids in adipose tissue including trans-9 16:1, which is a fatty acid that was previously associated with diabetes, did not modify the results. Conclusion: The observed inverse association between the cis-9, trans-11 CLA in adipose tissue and diabetes risk is consistent with the hypothesis that CLA may be involved in insulin regulation.